2017
DOI: 10.1016/j.jfda.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole residues in goat's milk: Interferences in microbial inhibitor tests used to detect antibiotics in milk

Abstract: Albendazole (ABZ) residues in goat's milk and their effect on the response of microbial inhibitor tests used for screening antibiotics were evaluated. A total of 18 Murciano-Granadina goats were treated with ABZ and individually milked once a day over a 7-day period. ABZ quantification was performed by high performance liquid chromatography. The ABZ parent drug was not detected. The maximum concentration of its metabolites (ABZ sulfoxide, ABZ sulfone, and ABZ 2-aminosulfone) was reached on the 1 day post treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Microbial inhibitor tests are widely used in laboratories for screening antimicrobials in milk because they are easy to use and inexpensive [51]. However, some substances present in milk can interfere with the test.…”
Section: Research Advances In Dairy Goat Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial inhibitor tests are widely used in laboratories for screening antimicrobials in milk because they are easy to use and inexpensive [51]. However, some substances present in milk can interfere with the test.…”
Section: Research Advances In Dairy Goat Productsmentioning
confidence: 99%
“…However, some substances present in milk can interfere with the test. No interference of antiparasitic drugs such as albendazole has been observed [51]. On the contrary, ivermectin residues in goat milk after parasite treatment altered the microbial inhibitor test [52].…”
Section: Research Advances In Dairy Goat Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results allow to conclude that the examined sample collected from local and frozen imported broilers giblets and tissue proved to be contaminated with residues of Oxy-tet + and Amp + especially in liver sample [ 2 ]. Romero et al [ 11 ] developed and described the method which concluded the effect of albendazole in goat milk and microbial inhibitor used of screening of antibiotics were evaluated with total of eighteen goats (Murciano-Granadina) treated with albendazole and collected milk from them after 7 days. HPLC is a technique used for identification and quantification of the albendazole and results found the albendazole was not detected but the metabolite of the same was found 1-day post-treatment lower than the Maximum Residual Limit (MRL) 100 μg/kg.…”
Section: Hplcmentioning
confidence: 99%
“…With increasing large-scale breeding, various parasitic diseases are seriously hindering economic output in the animal husbandry industry [1]. Many kinds of parasites infect animals, and parasites can parasitize various organs and tissues.…”
Section: Introductionmentioning
confidence: 99%